DAMPAK EKSPOSUR SCREEN TIME TERHADAP PERKEMBANGAN PSIKOSOSIAL PADA ANAK-ANAK PRASEKOLAH - Sarah Nabila Istiqomah (Journal Of Applied Health Research And Development, 2019)
The current era of globalization has led to advances in various fields and aspects of life, including technological development. Rapid technological developments cause changes such as the increasing use of gadgets in everyday life. The use of this gadget occurs in all ages, including children. The use of gagdget in children will cause exposure to screen time. Some studies suggest that exposure to screen time in children can cause various health problems, one of which is psychosocial development. This can be caused by disruption of sleep both quality and quantity and disruption of physical activity. Some studies mention the disruption of physical activity in children will make children's social interactions with themselves, family, and the environment unfavorable. Psychosocial development in preschool children can be influenced by several factors, one of which is interaction with others. This article aims to determine the impact of screen time exposure on psychosocial development in preschool children. Conclusions namely exposure of screen time will cause psychosocial development in preschool children.